Über die Auswirkungen des projektierten Hamburger Vorhafenbaus im Watt südlich des Elbeästuars - Klug, Heinz (ERDKUNDE, 1976)
The projected construction of an outer port of Hamburg and its connection by a dam with the mainland would lead to far-reaching hydrological-morphological changes in the tidal flats off Cuxhaven. An attempt has been made to record and assess these by relating the connections indicated by the present dynamics and development to the changed marginal conditions after the construction of the planned building-work, as identified by model-based investigations.